Маркетинг людських ресурсів та перспективи його реалізації для підприємств харчової промисловості - Грищенко, Діана Григорівна (My University, 2014)
У роботі обґрунтовано необхідність застосування маркетингу людських ресурсів як якісно нового рівня управління ними. Сформовано концепцію його реалізації, ключовим елементом якої є розроблений комплекс маркетингу людських ресурсів орієнтований на споживача, запропоновано методичний підхід оцінювання стану маркетингу людських ресурсів. Доведено вплив маркетингу людських ресурсів на ефективність діяльності підприємства та запропонованопрогресивні методи його реалізації з урахуванням етапів життєвого циклу працівника. This research focuses ontheoretical propositionsmarketingandhuman resourcedevelopmentresearch andpracticalrecommendations forimplementationby determiningthe prospects for itsimplementationfor the food industry. We provethe need to implementmarketinghuman resourcesas a qualitativelynew level ofhrmanagement. The author has formulated the concept ofhr-marketing implementation, a key element of which isthe complex ofhr-marketingfocused onconsumer.Methodical approach for its assessment has been created by the author too. The work describes the influence of the hr-marketing on the activity effectiveness of the company, that is why the author has showed the basis of advanced methods for hr-marketing implementation, taking into account the stages of the life cycle of an employee.
Keywords: підприємство; маркетинг; людські ресурси; маркетинг людських ресурсів; business; marketing; human resources; marketing ofhuman resources